Overvoltages on Power Filters under Energizing Industrial Power System Transformer - Yuriy Varetsky (Energy Engineering and Control Systems, 2020)
The practice of operating industrial power supply systems containing filter circuits has shown that filter tuning can have a significant impact on filter performance. On the basis of simulations of a real power supply system carried out by the Matlab / Simulink package, the results of a study of the impact of filter manufacturing tolerances on the filter transients under transformer energizing are presented. The most severe transients are observed for filter circuits in the power supply systems of electric arc furnaces due to frequently repeated operating energizing furnace transformers. This article summarizes the analysis of overvoltages on capacitors and reactors for various configurations of the filter circuit, arising during energizing the arc furnace transformer, taking into account the possible detuning of the filters.